A Comparative Study of Topiramate and Botulinum Toxin in Reducing Migraine Disability in Patients with Chronic Migraine - Solís-Tun, Erick-Eduardo; Piña-Ballantyne, Steven-Andrés; Arceo-Novelo, Jorge (British Journal of Healthcare and Medical Research, 2024)
Background: Chronic migraine (CM) is a highly debilitating neurological condition that requires effective treatment. Topiramate and botulinum toxin are widely used for management and prevention. However, comparative data on treatment escalation in patients with treatment-resistant CM and incobotulinum toxin A (inco-BTX-A, Xeomin®) remain limited. The Migraine Disability Assessment (MIDAS) questionnaire is a valuable tool for objectively quantifying the impact of migraines on daily functioning. This study aimed to conduct a comparative analysis of topiramate and inco-BTX-A in terms of their effectiveness in reducing disability associated with treatment-resistant CMs. Methods: This comparative, observational study evaluated the effectiveness of topiramate and botulinum toxin in reducing MIDAS scores in patients with CM who had previously failed initial treatments. Patients were divided into three groups: group 1 (topiramate to inco-BTX-A), group 2 (non-steroidal anti-inflammatory drugs/NSADIs to topiramate), and group 3 (NSAIDs to inco-BTX-A). Data collection included demographic features and MIDAS scores before and after treatment. Results: A total of 96 patients were included, with a predominance of female patients (85.41%). Group 1(n=39) showed a significant reduction in MIDAS scores 4.1 ± 2.88, t-statistic = 8.89 (p < 0.05). There was no significant difference between Group 2 (n=39) and Group 3 (n=18), with a p-value of 0.0545. Conclusions: Topiramate and inco-BTX-A effectively reduced MIDAS scores in patients with CM, particularly in those with treatment resistance. While groups 2 and 3 showed similar outcomes, inco-BTX-A demonstrated a more significant effect in group 1, suggesting its potential as an effective treatment for treatment-resistant CM.